Valorization of Plastic Waste in the Manufacture of Paving Stones in Congo Republic: The Case of Polyethylene Terephthalates (PET) - Berry, Ulrich; Motoula, Smäel Magloire Elombo; Samba, René Evrard Josué; Ndzessou, Westinevy Benarez (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study aims to contribute to the valorization of plastic waste—one of the leading contributors to environmental pollution—by proposing a practical recycling approach that utilizes waste plastics as a binder in road surfacing materials. Specifically, the research investigates the use of thermoplastic waste, with a focus on polyethylene terephthalate (PET), collected from the streets of Brazzaville, in the production of eco-friendly paving blocks. These blocks are composed of a sand matrix and contain 53.33% recycled plastic by weight. The study employed an experimental methodology, with water absorption rate as the primary performance indicator. The results indicate a consistently low water absorption rate across samples, regardless of variations in plastic content, suggesting a stable and durable material performance. These findings highlight the potential of recycled plastic-based paving blocks as a sustainable alternative for road surfacing, contributing to both waste reduction and infrastructure development.